Fabrication, characterization and comparison of DSSC using anatase TiO 2 synthesized by various methods - Umale, Sanjivani V.; Tambat, Sneha N.; Vediappan, Sudhakar; Sontakke, Sharad M.; Krishnamoorthy, Kothandam (Advanced Powder Technology, 2017)
In this study, anatase TiO2 nanoparticles were synthesized by three techniques, namely, sol-gel, acid-base co-catalyst and room temperature colloidal methods. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, pore diameter, pore volume and surface area. The dye-sensitized solar cells were fabricated using the synthesized materials and characterized for incident photon to current conversion efficiency, photocurrent density to photo voltage measurement and electrochemical impedance analysis. Among the studied materials, TiO2 synthesized by sol-gel method displayed highest photon to current conversion of 76.8% and a maximum solar cell efficiency of 7.85% with Jsc of 14.75mA/cm², Voc of 0.76V and FF of 0.7. This is the first study to report a high power conversion efficiency of DSSC using a sol-gel synthesized titania and its comparison with other two synthesized materials. The high power conversion efficiency of the solar cell using TiO2 synthesized by sol-gel method is attributed to its characteristic properties such high surface area, larger pore diameter and larger pore volume and highest dye loading capacity.